Hijrah and Islamic Movement in Indonesia: Sekarmaji Marijan Kartosuwiryo’s Perspective - Anwar Sanusi; Anisah Anisah; Didin Nurul Rosidin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeThe study aimed to understand the concept of Hijrah as perceived by Sekarmaji Marijan Kartosuwiryo or commonly known as Kartosuwiryo who was encouraged to establish the movement of Darul Islam/Tentara Islam Indonesia (DI/TII) as a jihad (struggle) against injustice in all life aspects of Indonesian citizen.MethodThe study applied historical research that comprised of four stages, namely heuristic, verification, interpretation, and historiography. The research relied on the primary data of newspaper articles, magazines, journal articles, books, and other written documents. The data were qualitatively analyzed to identify the concept of Hijrah that Kartosuwiryo perceived.Results/FindingsThe study revealed that Kartosuwiryo thought that Indonesia in the colonialization period was similar to the age of ignorance. The human exploitation through slavery and violence triggered to establish DI/TII movement to change Indonesia as Islamic state and implement Islam in all aspects of life.ConclusionThe study concluded that Kartosuwiryo perceived Hijrah as a jihad against injustice implemented through establishing DI/TII movement. It was intended to break the injustice in all life aspects of Indonesian citizens.